2017
DOI: 10.5152/dir.2016.15590
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced US-guided percutaneous biopsy of anterior mediastinal lesions

Abstract: A nterior mediastinal tumors are common in clinical settings. Common lesions include inflammatory vs. neoplastic lesions, benign vs. malignant lesions, and primary vs. metastatic lesions. Among these, lymphomas are medically treatable, thymomas are surgically treatable, and metastatic carcinomas are nonresectable (1). Primary mediastinal tumors represent only about 3% of the tumors within the chest wall. Metastatic carcinoma and non-Hodgkin's lymphoma are among common anterior mediastinal tumors. The rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
3
26
2
Order By: Relevance
“…Successful biopsy of AMMs and the achievement of a conclusive histological diagnosis with subclassification or genetic information are crucial for prompt treatment decisions in the era of personalized therapy [ 25 ]. The present and previous studies showed high diagnostic yields and low morbidity in the group that underwent US-CNB for AMMs [ 14 , 15 , 19 , 26 , 27 ]. All of these studies approved US as a standard guidance for biopsy procedures if AMMs can be imaged well by US.…”
Section: Discussionsupporting
confidence: 67%
“…Successful biopsy of AMMs and the achievement of a conclusive histological diagnosis with subclassification or genetic information are crucial for prompt treatment decisions in the era of personalized therapy [ 25 ]. The present and previous studies showed high diagnostic yields and low morbidity in the group that underwent US-CNB for AMMs [ 14 , 15 , 19 , 26 , 27 ]. All of these studies approved US as a standard guidance for biopsy procedures if AMMs can be imaged well by US.…”
Section: Discussionsupporting
confidence: 67%
“…In this systematic review, potential indications for CEUS‐guided biopsy were divided into 3 main categories: (1) biopsy from perfused areas to avoid necrosis; (2) biopsy of poorly visualized or downright “invisible” lesions; and (3) additional benefits from CEUS in relation to US‐guided biopsy. A total of 19 articles were identified …”
Section: Resultsmentioning
confidence: 99%
“…By directing the biopsy needle toward contrast‐enhanced areas within the target lesion, inadvertent sampling from necrotic parts of the tumor can be reduced. This strategy resulted in a 10% to 15% increase in diagnostic accuracy by a decrease in the false‐negative rate . The principle of this technique was first described in 2000 by Bang et al, in a small feasibility study using Levovist (Schering AG, Berlin, Germany) and real‐time sampling from enhancing areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is usually used for the biopsy of superficial lesions adjacent to the thoracic wall . Contrast‐enhanced ultrasound can clearly show tumor blood vessels and necrotic lesions, which can partially reduce the false‐negative rates of needle biopsy …”
Section: Methods For Imaging Guidancementioning
confidence: 99%